Transient free radicals studied by laser magnetic resonance spectroscopy - Gillett, D; Gillett, David Alan (1994)
﻿ A liquid nitrogen cooled, carbon monoxide laser magnetic resonance spectrometer was used to study mid-infrared vibration-rotation transitions in the gaseous free radical NCO, in its ̅X2Π state, at very high resolution. The use of an intracavity absorption cell made possible the observation of some transitions with sub-Doppler resolution. Developments to the spectrometer extended the range of operation of the CO laser. Most importantly, a CO laser operating on overtone transitions, Δν = 2, was operated in Oxford. The Δν = 2 CO laser operates over the range 2450-3800cm-1 (4.08-2.63 μm), and the Δν = 1 CO laser over the range 1200-2100 cm-1 (8.33-4.76 μm). NCO exhibits a Renner-Teller effect in its ground electronic state, an interaction between the motion of the electrons and the bending motion of the nuclei. Vibration-rotation transitions were observed in a sequence of bands involving the excitation of the out-of-phase stretching vibration, in the region of 1900cm-1. Some of the bands involved the excited bending vibration. The Zeeman effect behaviour of the molecular energy levels, particularly in the 2Σ vibronic states, clearly showed the manifestation of the Renner-Teller effect. The Zeeman effect in the 2Σ vibronic states was considered in detail. Many of the 2Σ LMR spectra were recorded at sub-Doppler resolution. NCO is complicated to model, and unassigned LMR spectra remain. A harmonic Renner-Teller model was developed for the analysis. It was implemented by constructing an explicit matrix representation of the single electronic state N2 effective Hamiltonian, which was diagonalised exactly. A new term in this Hamiltonian, describing centrifugal distortion corrections to the Renner-Teller coupling term, was developed for the 2Σ vibronic states in order to account for anharmonic vibronic interactions.